Inflammatory pseudotumour and Rosai-Dorfman disease of soft tissue: a histological continuum?. Issue 1 (January 1997) - Govender, D; Chetty, R
Abstract : A lesion of the chest wall in a 34 year old woman, which had a combination of histological and immunophenotypic features of inflammatory pseudotumor and Rosai-Dorfman disease of soft tissue, is described. There was considerable overlap in the pathogenesis, histology and immunophenotype of these two lesions. The similarities between these two lesions suggest that there is a temporal sequence and a histological continuum with early histiocyte-rich and late fibroblast- and myofibroblast-rich lesions. Alternatively, the morphological and immunophenotypic features could be because of aberrant cytokine expression in an inflammatory pseudotumour, resulting in transformation of histiocytes to resemble those seen in Rosai-Dorfman disease.